ANALYSIS OF THE INFLUENCE OF MULTINATIONAL, AUDIT QUALITY AND COMPANY SIZE ON THIN CAPITALIZATION OF MANUFACTURING COMPANIES LISTED ON THE IDX - Vonny Whidyawhati; Dian Purnama Sari (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2021)
Tax avoidance can be carried out through some schemes, one of them is through thin capitalization. Thin capitalization is a tax avoidance practice carried out by companies through financing their business from high debt instead of capital. In Indonesia, thin capitalization is first regulated in KMK-1002 / KMK.04 / 1984 which later changed to PMK 169 / PMK.010 / 2015. The purpose of this study is to analyze the effect of multinational, quality audits, and company size on thin capitalization. The research object includes manufacturing companies listed on IDX within the period of 2017 - 2019. The sample obtained includes 299 companies. This study uses secondary data in the form of financial reports. The data analysis technique used in this study is multiple regression analysis. The results show that multinational have no effect on thin capitalization, audit quality has negative effect on thin capitalization and firm size has positive effect on thin capitalization.